Resolving Fishing Disputes in Lubuk Larangan in Kuantan Singingi, Riau Province - Hengki Firmanda; Dina Imam Supaat; Mahmud Hibatul Wafi; Sudjito; Rika Lestari (Magister of Law, Faculty of Law, Universitas Mataram, 2024)
Volume 11, Issue 3